A Cross-sectional Study of Factors Affecting Quality of Life of People with Type 2 Diabetes - Mamahit, Citra Gabriella; Inaoka, Kimiko; Wariki, Windy Mariane Virenia; Ota, Erika (Pacific Rim International Journal of Nursing Research, 2023)
Diabetes is a chronic illness that negatively impacts quality of life. However, the quality of life of people with type 2 diabetes could be improved with sufficient literacy and abilities to perform self-management, such as managing blood glucose, maintaining a healthy diet, and proper exercise. This descriptive cross-sectional study aimed to describe the relationships among health literacy, self-management, and quality of life and to determine the predictors of quality of life of people with type 2 diabetes. Data were collected through purposive sampling from 218 individuals with type 2 diabetes in Manado City, Indonesia, between July and October 2021. We used the European Health Literacy Survey Questionnaire, Diabetes Self-management Questionnaire, and Diabetes Quality of Life Questionnaire. Data were analyzed using descriptive statistics, Pearson’s product-moment correlation, and hierarchical regression analysis. The study revealed that health literacy was significantly associated with self-management and quality of life. Furthermore, age, occupation, health literacy, and self-management were significant predictors and collectively explained 25.3% of the variance in quality of life. Hence, higher health literacy and improved self-management practices were linked to a higher quality of life for people with type 2 diabetes. Since the explained variance of quality of life in this study is only 25.3%, further studies should include other factors such as social and family support and communication with health care providers to predict quality of life. Nevertheless, nurses can use this study to design interventions to improve self-care management skills and health literacy levels, which may enhance quality of life. However, testing the effectiveness is needed.